2008
DOI: 10.1002/cyto.b.20408
|View full text |Cite
|
Sign up to set email alerts
|

Prednisone induces immunophenotypic modulation of CD10 and CD34 in nonapoptotic B‐cell precursor acute lymphoblastic leukemia cells

Abstract: Conclusions: The prednisone-induced immunophenotypic modulation can be reproduced in vitro and this phenomenon may reflect sensitivity to chemotherapy. q

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 14 publications
3
46
0
6
Order By: Relevance
“…Notably, CD34 expression was highly variable during follow-up and tended to reincrease in some patients already at day 33, a few days after start of tapering of GCs. This pattern of decrease and reincrease favorably matches with the schedule of GC containing chemotherapy as well as with the direction of the in vitro GC-induced expression alterations of these two antigens (11). It may therefore be regarded a transient, GC-induced phenomenon related to modulation of responsive genes and of the translational machinery, as discussed recently (19,20).…”
Section: Results and Discussion Evolution Of Antigen Expression Durinsupporting
confidence: 58%
See 3 more Smart Citations
“…Notably, CD34 expression was highly variable during follow-up and tended to reincrease in some patients already at day 33, a few days after start of tapering of GCs. This pattern of decrease and reincrease favorably matches with the schedule of GC containing chemotherapy as well as with the direction of the in vitro GC-induced expression alterations of these two antigens (11). It may therefore be regarded a transient, GC-induced phenomenon related to modulation of responsive genes and of the translational machinery, as discussed recently (19,20).…”
Section: Results and Discussion Evolution Of Antigen Expression Durinsupporting
confidence: 58%
“…The latter follow generic patterns, but occur with some interindividual variability (7). In this respect, we have recently shown that the amount of phenotypic shifts correlates positively with treatment sensitivity in ALL (11). Nevertheless, the good message for MRD studies is that phenotypic shifts of highly relevant antigens like CD10 and CD34 are only transitory and revert to initial aberrant patterns after stop of GC containing therapy in many patients (Fig.…”
Section: Drug-induced Phenotype Shifts In All Are Reversiblementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, improved characterization of the normal and leukemic cells will also facilitate the recognition of ALL cells despite the occurrence of immunophenotypic shifts, which frequently are apparent during the early phases of therapy. [38][39][40][41][42] Indeed, our current data show that 6-color FCM resulted in a higher concordance with molecular MRD data than 4-color FCM. Whereas using 4-color FCM 6% of samples were found to be positive by FCM only, this percentage dropped to almost 0% (0.2%) using 6-color FCM.…”
Section: -17supporting
confidence: 51%